2016
DOI: 10.1111/cea.12657
|View full text |Cite
|
Sign up to set email alerts
|

Dosing intervals in intralymphatic immunotherapy

Abstract: Allergen-specific subcutaneous (SCIT) as well as sublingual (SLIT) immunotherapy both confer long-term protection against the highly prevalent IgE-mediated allergies, such as allergic rhino-conjunctivitis and asthma. As both SCIT and SLIT are both very laborious and time-consuming treatments, we and others have investigated whether the immunotherapy could be enhanced by so-called intralymphatic immunotherapy (ILIT), which aims at improving treatment efficacy and safety and to shorten treatment duration, thereb… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
2
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 10 publications
0
2
0
Order By: Relevance
“…We have presented preclinical and clinical data describing intralymphatic immunotherapy (ILIT) with a recombinant allergen Feld1 fused to the 12‐mer HIV‐derived translocation sequence (GYGRKKRRQRRR) and to a part of the human invariant chain . This modular antigen transporter Feld1 (MAT‐Feld1) is efficiently taken up by antigen‐presenting cells .…”
mentioning
confidence: 99%
“…We have presented preclinical and clinical data describing intralymphatic immunotherapy (ILIT) with a recombinant allergen Feld1 fused to the 12‐mer HIV‐derived translocation sequence (GYGRKKRRQRRR) and to a part of the human invariant chain . This modular antigen transporter Feld1 (MAT‐Feld1) is efficiently taken up by antigen‐presenting cells .…”
mentioning
confidence: 99%
“…Since ILIT uses only 10% of the dose of SCIT, we may assume that anaphylaxis occurs 10 times less with ILIT than with SCIT due to the immunological response and the absence of mast cells in the lymph nodes. Indeed, studies have shown fewer adverse events [20][21][22][23]30] and less likelihood of anaphylaxis [35][36][37] with ILIT than with SCIT.…”
Section: Discussionmentioning
confidence: 99%
“…They found no clinical benefits from active ILIT. It has been debated that the short interval was not enough to make the immune system mature for the next injection compared with the need for intervals when vaccinating against infectious diseases [50]. It has also been suggested that this might have to do with too high a dose as the allergen may accumulate on shorter intervals.…”
Section: Ilit Against Birch Grass and Cedar Pollen Allergymentioning
confidence: 99%
“…Furthermore, when the intervals were narrowed to only two weeks and ILIT was administered three or six times, the clinical effect failed. It has been argued that the dosing interval between ILIT is essential [50,89]. However, narrowing the interval may also entail a higher dose.…”
Section: Efficacymentioning
confidence: 99%